Development Of Ship Archive Information System In XYZ Company With Scrum Methodology - Insanittaqwa, Vika; Putera, M. Ihsan Alfani; Shidiq, M. Fathurrahman (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
XYZ Company, a shipping agency in Balikpapan, handles the management of documents related to ships docking or sailing from the port. Currently, the document management process relies on manual, paper-based procedures, lacking a digital system to integrate all administrative processes. This manual approach is time-consuming, as staff need to search for and store physical documents in storage cabinets, which also occupy significant office space and pose a risk of document damage over time. The purpose of this research is to develop a web-based information system for document processing at XYZ Company, aiming to streamline the documentation process for ship archives. The development follows the Agile methodology using Scrum to adapt to evolving requirements throughout the development process. The stages of this research include Requirement Gathering, Sprint Planning, Daily Meetings, Sprint Reviews, Sprint Retrospectives, and Deployment. A total of 55 Product Backlogs were completed over three Sprints. Black Box testing was conducted at each iteration with the supervision of XYZ Company staff, yielding satisfactory results. The outcome of this research is an integrated Ship Archive Information System hosted on XYZ Company’s server, providing a robust solution to the ship documentation problem.